Laminoplasty for Cervical Spine Lesions - Tabe, Ryuji; Hirakawa, Syunichi; Totoribe, Koji; Fukuda, Kenji; Tajima, Naoya; Tashiro, Kouichi (Orthopedics & Traumatology, 1994)
Since 1984, cervical spinal canal enlargement has been performed in 41 patients with cervical myelopathy. Expansive open-door laminoplasty and double-door have been done. Clinical results were evaluated using the JOA score for cervical myelopathy and recovery rate using Hirabayashi's method. Radiologically, cervical measurement of antero-posterior movement by plane lateral films was carried out. We evaluated significant differences between the two different operative methods.